EFEKTIVITAS PENGGUNAAN QRIS UNTUK MENINGKATKAN AKSESBILITAS INFAQ DI MASJID RAYA DARUSSALAM PALANGKA RAYA - Anugrah Pangestu; Aufa Sholehah; Helda Pauziah; Hanief Monady (JOURNAL SAINS STUDENT RESEARCH, 2025)
This study aims to analyze the effectiveness of using QRIS (Quick Response Code Indonesian Standard) in collecting infaq and alms at the Darussalam Grand Mosque in Palangkaraya. Employing a descriptive qualitative method, data were obtained through interviews, observations, and documentation. The adoption of QRIS began during the COVID-19 pandemic as an effort to adapt to technological developments and to facilitate non-cash donations. The initiative was supported by Bank Syariah Indonesia (BSI), allowing congregants to give alms more practically and securely. From an Islamic legal perspective, the use of QRIS is permissible based on the principle of al-ashlu fi al-mu’amalat al-ibahah and is reinforced by a fatwa from the National Sharia Council (DSN-MUI) concerning sharia electronic money. The digital system enhances transparency and accountability in managing alms funds. This study concludes that QRIS improves donation convenience, increases the efficiency of fund collection, and demonstrates the integration of technology in worship practices.